Правовий звичай як основа укладання та розірвання шлюбу в Україні (XVIII-XX століття) - Шевченко, Д. А.; Shevchenko, D. A. (Право і суспільство. - 2021. - № 1, ч. 2. - С. 28-31, 2021)
Проаналізовано правові засади укладення та розірвання шлюбу в Україні у XVIII-XX столітті. Наголошено, що саме метричні книги на українських землях аж до XX століття були єдиним достовірним джерелом встановлення року народження, числа народжених та померлих, наявності факту вінчання і кількості раз вступу однією особою в шлюб і без них неможливо було дотримання цілого ряду умов укладення шлюбу. Тому, незважаючи на те, що парафіяльні священики не поспішали міняти свої звички, у XVIII столітті з'явилися обставини, які породжували відступ від основного правила укладення шлюбу ‒ церковного вінчання.

The scientific article is devoted to the study and comprehensive analysis of legal custom as a basis for marriage and divorce in Ukraine in the XVIII-XX centuries. Taking into account the doctrinal study, it stated that the ancient Slavic ideas about marriage as a contract between the parents of the bride and groom were quite ambiguous, because paternal authority and paternal word continued to remain in most first and last condition when deciding on marriage, but less, the effect of certain decrees, which began to be adopted in the XVIII century, was one of the steps aimed at protecting children from parental arbitrariness in the family. It is stated that in the XVIII century the principles of the Helmsman's book, marriage was preceded by engagement - an agreement during which the parents of the bride and groom agreed on the marriage and agreed on the dowry. A special record made out the engagement certificate. In case of violation of the promise to marry, a penalty was set, which sometimes reached significant amounts. At the same time, the priest made a crown record, which had presented during the wedding. For the primary solution in the field of family and marriage relations, Peter I chose two tasks: the deprivation of certain obsolete remnants of obligations in the field of property and the elimination of the religious obligation of church orders. Emphasis is placed on the fact that metric books were in the Ukrainian lands until the XX century were the only reliable source of establishing the year of birth, number of births and deaths, the fact of marriage and the number of marriages by one person and without them it was impossible to comply with a number of conditions. Marriage. Therefore, despite the fact that parish priests were in no hurry to change their habits, in the XVIII century there were circumstances that gave rise to a departure from the basic rule of marriage - a church wedding.

Проанализированы правовые основы заключения и расторжения брака в Украине в XVIII-XX веке. Отмечено, что именно метрические книги на украинских землях вплоть до XX века были единственным достоверным источником установления года рождения, числа родившихся и умерших, наличия факта венчания и количества раз вступления одним лицом в брак и без них невозможно было соблюдение целого ряда условий заключения брака. Поэтому, несмотря на то, что приходские священники не спешили менять свои привычки, в XVIII веке появились обстоятельства, порождавшие отступление от основного правила заключения брака – церковного венчания.
Legal custom as the basis of marriage and divorce in Ukraine (XVIII-XX centuries)
Шевченко, Д. А. Правовий звичай як основа укладання та розірвання шлюбу в Україні (XVIII-XX століття) / Шевченко Д. А. // Право і суспільство. - 2021. - № 1, ч. 2. - С. 28-31. -DOI: https://doi.org/10.32842/2078-3736/2021.1.2.5.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Цивільне право. Civil Law. Гражданское право; Україна. Ukraine. Украина; Історія. History. История; шлюб; marriage; брак; сім’я; family; семья; шлюбно-сімейні відносини; marital and family relations; брачно-семейные отношения; укладення шлюбу; заключение брака; сімейні правовідносини; family legal relations; семейное правоотношение; правовий звичай; правові засади; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ